Daredevil by mark waid (2011), volume 7 ebook - Waid, Mark (Daredevil by Mark Waid (2011), 2018)
Collects Daredevil (2011) #31-36. The Serpent Society has been buying off the New York justice system and using it to their own sinister means. The only man that stands in their way? Matt Murdock, the man known as DAREDEVIL! It's Daredevil versus the Sons of the Serpent in an all-out battle for the soul of truth and justice in New York City!